The relationship between cardiac dimensions, VO2max and fat free mass in two standards of swimmers - Heshmat, H.; Basyony, T. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The objective of the study was to investigate echocardiography in exploring the relationship between cardiac dimensions, Vo2 max and FFM in two standards of swimmers (according to Vo2 max and swim records).